Cote D'Ivoire : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Requests for Modification of Performance Criteria and Extension of the Current Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Cote d'Ivoire's Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility (ECF) and Requests for Modification of Performance Criteria (PC) and Extension of the Current Arrangement. Program performance has been strong. All end-December PCs and all but one indicative target were met. On the downside, fiscal discipline and structural reform momentum could be adversely affected during the run-up to the October 2015 presidential elections. The IMF staff supports the completion of the fifth review under the ECF and the authorities' requests for the modifications of PCs and an extension of the current arrangement to end-December 2014.